Hantavirus diseases pathophysiology, their diagnostic strategies and therapeutic approaches: A review. (28th September 2020) - Munir, Naveed; Jahangeer, Muhammad; Hussain, Shoukat; Mahmood, Zahed; Ashiq, Mehvish; Ehsan, Fatima; Akram, Muhammad; Ali Shah, Syed Muhammad; Riaz, Muhammad; Sana, Aneezah
Abstract: Hantaviruses are enveloped negative (−) single‐stranded RNA viruses belongs to Hantaviridae family, hosted by small rodents and entering into the human body through inhalation, causing haemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS) also known as hantavirus cardiopulmonary syndrome (HCPS). Hantaviruses infect approximately more than 200 000 people annually all around the world and its mortality rate is about 35%–40%. Hantaviruses play significant role in affecting the target cells as these inhibit the apoptotic factor in these cells. These viruses impair the integrity of endothelial barrier due to an excessive innate immune response that is proposed to be central in the pathogenesis and is a hallmark of hantavirus disease. A wide range of different diagnostic tools including polymerase chain reaction (PCR), focus reduction neutralization test (FRNT), enzyme‐linked immunosorbent assay (ELISA), immunoblot assay (IBA), immunofluorescence assay (IFA), and other molecular techniques are used as detection tools for hantavirus in the human body. Now the availability of therapeutic modalities is the major challenge to control this deadly virus because still no FDA approved drug or vaccine is available. Antiviral agents, DNA‐based vaccines, polyclonal and monoclonal antibodies neutralized the viruses so these techniques are considered as the hope for the treatment of hantavirus disease. This review has been compiled to provide a comprehensive overview of hantaviruses disease, its pathophysiology, diagnostic tools and the treatment approaches to control the hantavirus infection. Abstract : A graphical abstract representing the selection of data to compile the hot issue of Hantavirus associated diseases using different keywords. Then how the most relevant literature were selected using different key words. Major outlines are represented in the graphical form including Reservoir, Transmission and Replication of Virus, Pathophysiology of Diseases, Diagnostic Strategies and Therapeutic Approaches to make the article attractive for researchers and readers. Final it is represented that HFRS and HPS are major diseases associated with Hantavirus and conclusion explored that although a wide range of Diagnostic and Preventive measures are available but Drug Development is the Major Challenge required more attention.